Strategi Manajemen Penyelesaian Skripsi Sebagai Upaya Peningkatan Mutu Tugas Akhir Mahasiswa di Unital - Soares, Inacio Antonio; Shunhaji, Akhmad; Afif, Nur (Riviera Publishing, 2025)
This study aims to analyze the management strategy of thesis completion as an effort to improve the quality of students' final projects at Universidade Oriental Timor Loro Sae (UNITAL), with a focus on the Faculty of Education. This research is motivated by the discovery of delays in thesis completion, inconsistencies in the guidance process, and variations in the quality of students' final projects. The focus of the research is directed at four main management functions, namely planning, implementation, supervision, and evaluation in the thesis guidance process. The research method used is a descriptive qualitative approach, with data collection techniques through direct observation, in-depth interviews with supervisors, faculty leaders, and students, as well as documentation studies on academic guidelines and thesis completion archives. The results of the study show that an effective thesis completion management strategy includes structured and measurable guidance scheduling, improving the competence of supervisors through research methodology training, providing responsive and accessible academic services, and utilizing a digital monitoring system to monitor student progress. The implementation of this strategy has proven to contribute significantly to improving the quality of thesis substance, timeliness of completion, and student academic discipline. This study emphasizes that optimizing the management of thesis completion is a key factor in improving the academic quality of students as a whole and supporting the achievement of academic standards of the Faculty of Education at UNITAL.